Pengaruh Kemasan Produk Terhadap Harga Jual Produk Pada Dream Snack Sukabumi (Studi Kasus Pada UD Saputra Jaya Sukabumi): Manajemen pemasaran - Neneng Yanti Andriani & Sopian Syawa (P3M STIE PASIM Sukabumi, 2020)
This study examines The Infuence Of Product Packaging On Product Selling Price at Dream Snack Sukabumi (Case Studi at UD.Saputra Jaya Sukabumi), the research method used is descriptive analysis and associative analysis, the type of technique used by the probability sampling technique means sampling technique that provide equal opportunities for each element or memberof the population to be selected as samples. The technique used in determining the number of samples is to use the saturated sampling method. The result of the correlation value of the influence of Product Packaging (X) on the selling Price of the Product (Y) at Dream Snack Sukabumi (Case Studi at UD Saputra Jaya Sukabumi) amounted to r = 0822, which means it is between the range 0.76-1.00, which means a very strong, the nature of the relationship is positive, which means that if the packaging product owned by the company is more attractive then the selling price of the product will be better and increase, the nature of the influence of product packaging on the selling price of the product (+) means that the product packaging increases, for the resultsof the determination coeffecient or R Square is 67.57% on the selling price of the product, while the remaining 32.43% is needed by variabel other than product packaging variabel needed in the study. The result regression analysis value Y= 0.378 + 0.838 X The constantvalue of 0.378 point states that if there is no change in the packaging of UD Saputra Jaya Sukabumi product (0/None) then the value of the product selling price is 0.378 point. While the regression coefficient of X is 0.838 point, stating that every increase in packaging that is increasingly attractive one time or increasing once on product at UD. Saputra Jaya Sukabumi..